Implementing value capture in Latin America : policies and tools for urban development - Smolka, Martim Oscar (Policy focus series (Lincoln Institute of Land Policy), 2013)
This report provides a review of land value capture's antecedents in Latin America and itslongstanding presence in the urban planning agenda. It also examines a variety of landvalue capture instruments including: property taxation and betterment contributions;exactions and charges for building rights; and large-scale approaches such as thedevelopment of public land through privatization or acquisition.